Necessity of changing the wrong understanding of bioethics in today’s biopolitical reality – Or: Are the Balkans already infected with Sicko Virus? - Donev, Dejan (Academia Verlag, Sankt Augustin, 2012)
... In countries which went through the painful transitional route from one to another social system, the unavoidable need of reforms in many social spheres of life is too obvious. Beside educational, political, economical..., there is still the reform of health system for which, not only from ideological and political aspects, many analysts question: does Sicko already come on Balkan beside the fact that we had or still have a good social health system... From here, what the text sets and tries bioethically to discuss is the question: Can we treat the reforms of health system only as an economical and political question or they are making or made in interest of improving the quality of health services, in another words in interest of protection and improvement of human life and health? If we give an affirmative answer to the first part of the question, we are able to create and adequate health policies in one country where if you don’t have enough money you must choose in accordance to the limits of your family budget, and also as you are getting older you are less interest for exploitation inside the social system - similar to the examples given in SICKO model. If we give an affirmative answer to the second part of the question then we must from the start develop and implement the right concept of understanding bioethics as an ethics which is globally founded on “bios” and its highest value - life, and from there to start in creation of adequate health policies exemplary to the specifics of the same country, in another words EVERY LIFE IS WORTH LIVING! At the very end, if we make or made health reforms like this, which are possible if we also include the process of making politics and economy more and more (bio)ethically, the result is more than evident: instead SICKO, we will exceed today’s condition of biopolitical and will direct ourselves to the “practical rethinking of the field of political; to the new affirmation of philosophy; and to dehumanization of living world”. In the same time it will be a positive confirmation to the question: can we come to good health policy and reforms through implementation of the right concept of bioethics - LIFE BEFORE AND ABOVE ALL!